Pengetahuan, Sikap dan Motivasi Remaja Putri tentang Deteksi Dini Kanker Payudara melalui Sadari di SMPN 13 Tanjung Jabung Timur - Ratna Jelita Sari; Sulastri Sulastri (Jurnal Akademika Baiturrahim Jambi, 2022)
According to GLOBOCAN data (IARC) in 2012 it is known that breast cancer is a cancer with the highest percentage of new cases (after controlling for age), which is 43.3%, and the percentage of deaths (after controlling for age) due to breast cancer is 12.9 %. This research is a correlation analytic study with a cross sectional design. The population in this study were 145 teenage girl. The sampling technique used is simple random sampling namely 59 sampling, where the research was conducted by filling out a questionnaire, analyzed using univariate and bivariate analysis. The results of this study showed that from 59 respondents, the majority of respondents had poor knowledge, namely 36 respondents (61%), the majority of respondents had a negative attitude, namely 45 respondents (76.3%), the majority of respondents had low motivation, namely 31 respondents (52.5 %) and there is a significant relationship between knowledge, attitude and motivation of young women and early detection of breast cancer through BSE at SMP N 13 Tanjung Jabung Timur with p values of 0.000, 0.000 and 0.001 respectively.